Pengaruh Sanksi Pajak dan Tarif Pajak terhadap Kepatuhan Wajib Pajak UMKM di Jagakarsa, Jakarta Selatan - Faiz Rizky Ramdani; Erni Prasetiyani (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to examine the effect of tax sanctions and tax rates on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) in Jagakarsa, South Jakarta. The research uses a quantitative approach with a sample of 98 respondents selected using the Slovin formula. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression, F-test, R-squared test, and t-test. The findings show that tax sanctions have a significant positive effect on tax compliance with a t-value of 4.050 > t-table value 1.660, and a determination coefficient of 51.9%. Similarly, tax rates significantly affect compliance with a t-value of 6.130 > t-table value 1.660, and a determination coefficient of 59.5%. Simultaneously, tax sanctions and tax rates significantly influence compliance with an R-squared value of 64.8% and a regression equation of Y = 0.225 + 0.420X1 + 0.483X2 + e. These results highlight the importance of fair enforcement and balanced tax policies to improve taxpayer compliance among MSMEs.